Milosz Miszczynski and Adriana Helbig, eds. 2017. Hip Hop at Europe's Edge: Music, Agency, and Social Change. (24th October 2018) - Wilson, Dave
Abstract : Milosz Miszczynski and Adriana Helbig, eds. 2017. Hip Hop at Europe's Edge: Music, Agency, and Social Change. Bloomington and Indianapolis: Indiana University Press. 311pp. ISBN 978-0-25302-304-9 (pbk).